Native plant naming by high-school students of different socioeconomic status: implications for botany education - Bermudez, Gonzalo M. A.; Díaz, Sandra; De Longhi, Ana L. (International Journal of Science Education, 2018)
People’s diminished awareness of plants, affected by anthropogenic environmental deterioration, has challenged science education to overcome the obstacles impeding a better understanding of their meaning and value. The aim of this study was to investigate the influence of the socioeconomic status of high-school students, as indicated by their attendance at private or state schools, on their knowledge of native plants. In total, 321 students aged 15–18 were asked to write down 10 plants native to Córdoba, Argentina, in a freelist questionnaire. Students listed a mean of 6.8 species of a total of 165 different categories of plant names. The majority of the species named were exotic to Córdoba (63%) or Argentina (50.6%, of which 33.8% were adventitious), indicating an ‘adventitious-to-native’ effect by which all spontaneously reproducing plants were presumed to be native species. However, the 20 most frequently named plants were mainly native, with ‘Algarrobo’ (Prosopis spp.) and ‘Espinillo’ (Vachellia caven) being the most mentioned. Students’ socioeconomic status had a significant effect on the number of species named, with the students of state schools (where the less well-off sectors of the society attend) mentioning more species and, among these, more native ones than the students from private schools. Furthermore, we defined size, colour and scent as being conspicuous traits of plant flowers that are relevant for human perception, and found that the most frequently named adventitious species, unlike the native ones, were those exhibiting big brightly-coloured flowers which ranged from being inodorous to having medium intensity scents.
Keywords: Botany teaching; biological diversity; floral traits; plant blindness; school sector